Increasing charging energy at highly congested commercial charging sites through charging control with load balancing functionality. (15th November 2022) - Simolin, Toni; Rauma, Kalle; Rautiainen, Antti; Järventausta, Pertti
Highlights: Load balancing at highly congested charging sites is studied. A novel phase-specific control is developed to mitigate load unbalance. The developed control method outperforms the previously proposed solution. The control method increases the charging operator's profits up to 6% The control method achieves higher benefits in case of higher congestion. Abstract: It is expected that a notable share of charging sites will face significant congestions in the future, and thus, an effective utilization of the available charging capacity will be highly needed. It has been shown that unbalanced electric vehicle (EV) charging loads may reduce the charging energy, which can lead to a reduced quality of charging service and charging site operator's profits. To overcome the issue, this paper considers two solutions that allows the charging site to control the phase load balance: phase reconfiguration and a novel phase-specific control. Extensive simulations are carried out to investigate the benefits of the solutions. The results clearly indicate that the control methods have a notable potential in increasing the charging energy and quality of the charging service in highly congested charging sites. According to the simulation results, the phase-specific control leads to up to 5.9% higher revenue whereas the phase reconfiguration increases the revenues by up to 4.1% when compared with the baseline scenario without any load balancing functionality. The results also show that the more congested the charging site is, the higher benefits of the phase-specific control can be seen. Furthermore, the results show that assuming perfectly balanced three-phase loading yields unrealistically high charging energy in the congested charging sites, and thus, it is discouraged to use this assumption in future studies.